Neuropsychiatric Symptoms and Risk of Progression to Alzheimer's Disease Among Mild Cognitive Impairment Subjects - Dietlin, Simon; Soto, Maria; Kiyasova, Vera; Pueyo, Maria; de Mauleon, Adelaïde; Delrieu, Julien; Ousset, Pierre Jean; Vellas, Bruno (Journal of Alzheimer's disease, 2019)
Neuropsychiatric symptoms (NPS) are prevalent in mild cognitive impairment (MCI), but we do not know much about their role in progression to dementia. To investigate NPS and the risk of progression to probable Alzheimer's disease dementia (AD) among subjects with MCI. 96 MCI participants were followed for 4 years. Progression to probable AD was defined by the change of CDR total score from 0.5 to ≥1, reviewed by an expert consensus panel. NPS were determined using the Neuropsychiatric Inventory (NPI) 12-items. This study analyzed prognostic value of each NPI item and 5 sub-syndromes of NPS (apathy, psychosis, affective, hyperactivity, and vegetative) for prediction of progression to probable AD. A Cox proportional hazard model was used; hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated with time dependent variable to compare the incidence of progression considering presence/absence of any NPS or sub-syndromes throughout the study. The presence of symptoms "agitation/aggression", "delusions", and "aberrant motor behavior" significantly increased the risk of probable AD (HR = 3.9; 95% CI = 1.9-8.2; HR = 13.9; 95% CI = 4.1-48.9; HR = 4.3; 95% CI = 1.7-10.3, respectively). The presence of sub-syndromes "psychosis" and "hyperactivity" were also predictors of progression (HR = 14.0; 95% CI = 4.4-44.5; HR = 2.0; 95% CI = 1.1-3.7, respectively). These results did not change after adjusting by potential confounders. Presence of delusions, agitation/aggression, and aberrant motor behavior is predictor of progression to probable AD.